Eosinophils enhance WNT-5a and TGF-β(1) genes expression in airway smooth muscle cells and promote their proliferation by increased extracellular matrix proteins production in asthma - Januskevicius, Andrius (BMC Pulm Med, 2016)
BACKGROUND: Recent studies have suggested that eosinophils may have a direct effect on airway smooth muscle cells (ASMC), causing their proliferation in patients with asthma, but the precise mechanism of the interaction between these cells remains unknown. We propose that changes in Wnt signaling activity and extracellular matrix (ECM) production may help explain these findings. Therefore, the aim of this study was to investigate the effect of eosinophils from asthmatic and non-asthmatic subjects on Wnt-5a, transforming growth factor β(1) (TGF-β(1)), and ECM protein (fibronectin and collagen) gene expression and ASMC proliferation. METHODS: A total of 18 subjects were involved in the study: 8 steroid-free asthma patients and 10 healthy subjects. Peripheral blood eosinophils were isolated using centrifugation and magnetic separation. An individual co-culture of eosinophils with human ASMC was prepared for each study subject. Adhesion of eosinophils to ASMC (evaluated by assaying eosinophil peroxidase activity) was determined following various incubation periods (30, 45, 60, 120, and 240 min). The expression of Wnt-5a, TGF-β(1), and ECM protein genes in ASMC was measured using quantitative real-time polymerase chain reaction (PCR) after 24 h of co-culture. Proliferation of ASMC was measured using the Alamar blue method after 48 h and 72 h of co-culture with eosinophils. RESULTS: Eosinophils from asthmatic subjects demonstrated increased adhesion to ASMC compared with eosinophils from healthy subjects (p < 0.05) in vitro. The expression of Wnt-5a, TGF-β(1), collagen, and fibronectin genes in ASMC was significantly higher after 24 h of co-culture with eosinophils from asthmatic subjects, while co-culture of ASMC with eosinophils from healthy subjects increased only TGF-β(1) and fibronectin gene expression. ASMC proliferation was augmented after co-culture with eosinophils from asthma patients compared with co-culture with eosinophils from healthy subjects (p < 0.05). CONCLUSIONS: Eosinophils enhance Wnt-5a, TGF-β(1), fibronectin, and collagen gene expression in ASMC and promote proliferation of these cells in asthma. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02648074.